Pendampingan Pembuatan Kemasan, dan Pemasaran Digital Pada Industri Abon Ikan di Desa Obel-Obel Kecamatan Sambelia - Abdul Khalik; Abdul Chalel Rahman; Salmi Yuniar Bahri; Baiq Puspita Lestari Putri; Sultanil Jamil; Sri Apriani Damayanti (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This study aims to enhance the competitiveness of fish floss SMEs in Obel-Obel Village, Sambelia District, through training on packaging design and digital marketing. Local SMEs often struggle to compete with factory-made products due to less attractive packaging and conventional marketing strategies. The training was conducted using lectures, practical sessions on design using the Canva application, and the introduction and utilization of social media platforms such as Facebook, Instagram, TikTok, and WhatsApp as digital marketing tools. The results of the program show an improvement in participants' understanding of digital literacy, basic packaging design, and their ability to leverage digital platforms for product promotion. Additionally, participants received knowledge on health standards and product labeling from the Lombok Timur Health Office. This PKM has successfully encouraged local SMEs to innovate in product packaging, build brand awareness, and expand their market reach through digital media.